Relationships among ecological traits of wild bee communities along gradients of habitat amount and fragmentation. Issue 1 (14th December 2016) - Carrié, Romain; Andrieu, Emilie; Cunningham, Saul A.; Lentini, Pia E.; Loreau, Michel; Ouin, Annie
Abstract : Amount of semi‐natural habitats (permanent grasslands, woodlands and hedgerows) and their level of fragmentation are among the main determinants of wild bee diversity in agricultural landscapes. However, their impact on the distribution of bee ecological traits has received little attention. In this study, we aimed to explore whether changes in the distribution of bee ecological traits along gradients of habitat amount and fragmentation were due to a direct effect of landscape context on multiple traits ('response traits') or to a correlation of response traits with other ecological traits not involved in the response of bee species to landscape context. In two study regions in southwest France and southeast Australia, we used a RLQ analysis (three‐table ordination method) to link bee traits with habitat amount and fragment isolation measured at the landscape scale. We found that bee ecological traits shifted at the community‐level in association with landscape gradients, whereas species‐level associations among bee traits and phylogenetic clustering in bee communities were of only minor importance in determining such shifts. We found that traits such as body size and nest location were closely linked to habitat amount and fragmentation. We also observed regionally‐specific relationships among ecological traits, suggesting that the regional species pool can play an important role in determining the response of bee communities to habitat amount and fragmentation. Our findings suggest that improved knowledge about how trait‐based responses mediate the impact of landscapes on wild bee communities will allow better prediction and understanding of subsequent effects on ecosystem functioning.